A study of risk factors and their correlation with severity of retinopathy of prematurity: a prospective study - Yelameli, Bhuvaneshwari C.; Neelannavar, Ramesh V.; Das, Kiruthika (International Journal of Contemporary Pediatrics, 2020)
Background: Recent advances in neonatal care in the last decade and improved survival rates have resulted in an apparent increase in the incidence of retinopathy of prematurity (ROP), which is the most important cause of preventable blindness in infants. This study was done to identify the risk factors which predispose to ROP and to assess its correlation with severity of ROP. Methods: A total of 140 neonates with gestational age ≤34 weeks, birth weight ≤2000 grams who were admitted at NICU, S. N. Medical College and HSK Hospital, Bagalkot from December 2018 to May 2019 were considered. Babies were assessed and recorded for the risk factors of ROP in a predesigned proforma. ROP screening was performed using wide-field digital imaging on a retcam shuttle (Clarity MSI, USA). Results: A total of 140 babies were examined, and an overall incidence of ROP was 52 (37.1%). 17 (32.7%) had stage 3, 3 (5.8%) had stage 4, and 1 (1.9%) had stage 5. Among the 52 babies with ROP, 19 (51.3%) underwent laser photoablation. Risk factors like gestational age, birth weight, maternal risk factors, apnea, intrauterine growth restriction (IUGR), hypoglycaemia, respiratory distress syndrome (RDS), sepsis, coronary heart disease (CHD), blood transfusion and oxygen requirement duration were significantly associated with ROP. Delay in the establishment of feeds has been associated with ROP (p<0.001). Conclusions: Screening should be intensified in the presence of risk factors which can reduce the incidence of severe stages of ROP as highlighted by this study.